2019
DOI: 10.1074/mcp.ra118.001133
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic and Functional Analyses Reveal Sperm-specific Protein Changes Downstream of Kappa Opioid Receptor in Human Spermatozoa

Abstract: The phosphoproteome downstream KOR has been studied in human spermatozoa by applying quantitative MS-based proteomics. This studies have been combined with functional approaches to analyze the role of the receptor in the sperm physiology. Results reported phosphorylation changes in spermspecific proteins as well as the inhibition of sperm motility and acrosome after the addition of U50488H, the specific ligand. Graphical Abstract Highlights• Insights into molecular mechanisms underlying GPCR in human spermatoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 66 publications
3
27
0
Order By: Relevance
“…The 1632 phosphopeptides consisted of mainly phosphorylated S residues (80%), followed by phosphorylated T (11%) and Y (9%) residues ( Figure 2 a). A previous study identified a total of 3303 phosphorylated sites [ 8 ] and 3527 phosphorylated sites [ 9 ] in sperm in humans but not in mice. The phosphopeptides identified in this study were then compared with data on PhosphoSitePlus, which provided evidence of 1050 novel phosphosites that have not been previously characterized in mouse sperm ( Supplementary Data 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1632 phosphopeptides consisted of mainly phosphorylated S residues (80%), followed by phosphorylated T (11%) and Y (9%) residues ( Figure 2 a). A previous study identified a total of 3303 phosphorylated sites [ 8 ] and 3527 phosphorylated sites [ 9 ] in sperm in humans but not in mice. The phosphopeptides identified in this study were then compared with data on PhosphoSitePlus, which provided evidence of 1050 novel phosphosites that have not been previously characterized in mouse sperm ( Supplementary Data 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on human sperm incorporating phosphoproteomics followed by bioinformatics have identified many novel phosphosites on different proteins, such as CABYR, AKAP3, and AKAP4 [ 8 , 9 ]. One study on boar based on proteomics coupled with ingenuity pathway analysis (IPA) has provided a model of molecular mechanisms, showing that ODF, SPAG6, and AKAP4 affect sperm motility and fertility [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We confirmed the presence of KIF9 at the protein level in the spermatocytes using an antipeptide antibody. Proteomic studies have revealed the presence of KIF9 in human sperm [12][13][14] as well as sperm of several mouse species [15]. Thus, based on studies in lower organisms and localization in mammalian sperm, we anticipated that there would be a strong motility defect.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that a more rigid swimming pattern was also noted for sperm lacking the sperm specific isoform of calcineurin [16], along with a defect in fertilization capability. KIF9 has been found to be phosphorylated [13], and thus it is possible that regulation of KIF9 by phosphorylation contributes to the regulation of the flagellar waveform.…”
Section: Discussionmentioning
confidence: 99%
“…One way sperm sense their environment and respond accordingly is through signal-transduction pathways. Urizar-Arenaza et al (26) studied a class of metabotropic receptors, G-protein coupled receptors (GPCRs), a large class of biomolecules that respond to external stimuli and transduce signals across membranes. GPCRs are well known in a broad variety of biological processes although their specific roles in sperm physiology and function are not well studied.…”
mentioning
confidence: 99%